Comparison of Heavy Metal and Trace Element Levels in Inferior Nasal Concha of People Living in Rural and Urban Regions - Fatih Öner; Nezahat Kurt; Harun Üçüncü (Galenos Yayinevi, 2025)
Heavy metal exposure has recently become a problem due to the increasing environmental pollution as urbanization expands. This prospective cross-sectional study was conducted to compare levels of heavy metals in the nasal concha of the patients living in urban and rural who underwent partial inferior concha resection.Sixty-seven patients were divided into two groups: 38 rural patients and 29 urban patients. Partial inferior turbinate resection was performed in these patients with turbinate hypertrophy, and these tissues were examined for heavy metal levels. Lead (Pb), cadmium (Cd), zinc (Zn), copper (Cu), and manganese (Mn) levels were measured in inferior nasal concha by inductively coupled plasma- optical emission spectrometry.The levels of Cu (0.24±0.048 vs. 0.06±0.019 μg/g) and Zn (3.29±0.69 vs. 0.44±0.14 μg/g) of the rural patients were significantly higher compared to urban patients (p<0.001). There was no significant difference in the Cd level between groups. Pb (0.024±0.009 vs. 0.008±0.0002 μg/g) and Mn (0.273±0.01 vs. 0.174±0.05 μg/g) levels of urban patients were significantly higher than rural patients (p<0.001). Significance was considered at p<0.05.Heavy metals accumulate in the nasal concha at different rates in rural and urban areas. In pathologies with unclear pathophysiology and potential for heavy metal accumulation, such as air pollution, it may be helpful to indicate the presence of heavy metals in the nasal turbinate's and measure their amounts for diagnostic purposes.
Keywords: nasal mucosa; inductively coupled plasma-optical emission spectroscopy; Otorhinolaryngology; RF1-547; air pollution; spectrophotometry; turbinates; heavy metals; Original Investigation